Choreographing Matrilineal Archives: Feminist Emplacement in Perempuan dan Rumah Gadang by Loravianti - Hendra Nasution; Wiwik Sushartami; Rr Paramitha Dyah Fitriasari (Gondang: Jurnal Seni dan Budaya, 2025)
This research examines the choreographic work of Susas Rita Loravianti, particularly Perempuan dan Rumah Gadang, as sites of feminist resistance and spatial emplacement within the Minangkabau village. While existing scholarship on Minangkabau often romanticizes its matrilineal system, this study identifies a gap in understanding how women's bodies actively negotiate the matrilineal paradox, the tension between symbolic female power in the ancestral home and formal male authority in public discourse. Drawing on a two-year ethnographic approach (2022–2024), the research employs participant observation, semi-structured interviews, and detailed gestural mapping to analyze the creative process. The study integrates Doreen Massey's concept of relational space with Gay McAuley's performance spatiality to argue that Loravianti's choreography transcends mere illustration, constituting a subversive critical perspective that reimagines the village (kampuang) as a dynamic arena of global social relations. The findings suggest that the performance functions as a subaltern counterpublic, empowering women to develop oppositional identities in opposition to the restrictive behavioral codes of the Sumbang Duo Baleh. Furthermore, the research considers the limitations of this artistic strategy, questioning the inclusivity of the performance space for non-elite women within the village and examining the potential for artistic abstraction to obscure pressing socio-political crises.